Authentication and overhearing to prevent internal and external attacks in WSN - Maidhili R, Siri; GM, Karthik (International Journal of Engineering and Technology, 2018)
Wireless Sensor Networks are usually the assortation of sensors, which are versatile in sensing the data based on multihued exertions. The cardinal bulge with the sensor networks is its dispersed nature. Since they are spread over, they sense and forward data from their dispersed areas. They consume high energy resources and vulnerable to various attacks. To prevail this bulge, source identity (signature) based authentication scheme is proposed on ECC to prevent external attacks and a neighbor monitoring scheme is proposed by overhearing to prevent internal attacks. Now the cardinal strike with the sensor networks are its bounded energy resources, they have a very limited / less energy resources, they cannot have a hefty application assignment. To prevail this strike and to improve the energy efficiency, a low energy consumption MAC protocol is acquainted called the IEEE 802.15.4 / ZigBee standards un the MAC layer, through which the data forwarding among the networks devours very low energy when compared to all other traditional methods. The main objective of the proposed work is to perform broadcast after authentication, to prevent resource consuming attacks through authentication externally and to construct a monitoring table for each node by overhearing and detecting them based on their activities if they are malicious to provide internal security to the network. The proposed work attains a minimal energy wastage along with security integrated in WSN communication. The ratio of efficiency comparisons of the broadcasting authentication scheme and monitoring scheme for the traditional and the proposed works for the factors secure authentication / monitoring and energy consumption is resulted to be as 7:2. Thus the proposed system has a higher endorsed based on the generated results.